PARENTING CHILDREN WITH SEPARATION ANXIETY DISORDER: FATHER INVOLVEMENT AND PARTICIPATION - Yubaedi Siron; Tiara Anggraini; Maulia Amandasari (Universitas Nahdlatul Ulama Surabaya, 2023)
Father involvement in parenting is an important factor in the process of children's growth and development.This study aims to explore and find out how fathers are involved in parenting the children with separationanxiety disorder. The qualitative method is employed in this research. This study included structuredinterviews for data collection. Purposive sampling was used to choose participants. Three fathers whosechildren with Separation Anxiety Disorder (SAD) involved in this study. The results showed that theinvolvement of fathers in childcare plays an essential role in the development of children with SAD. Fathershave done a good role in parenting for SAD children, as well as a good relationship between fatherand children with SAD. Fathers have varied activities to stimulate their SAD children, such as positivecommunication comes from fathers to their children. Fathers give good understanding to their childrenand provide follow-up on their parenting participation and involvement. This study contribute to themodel of father involvement in special needs children, especially children with separation anxiety disorder.